2020
DOI: 10.1111/1346-8138.15618
|View full text |Cite
|
Sign up to set email alerts
|

Guidelines for the management of dermatomycosis (2019)

Abstract: The "Guidelines for the management of dermatomycosis" of the Japanese Dermatological Association were first published in Japanese in 2009 and the Guidelines Committee of the Japanese Dermatological Association revised it in 2019. The first guidelines was prepared according to the opinions of the Guidelines Committee members and it was of educational value. The revised version is composed of introductory descriptions of the disease concepts, diagnosis, medical mycology and recent advances in treatment, along wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
48
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 40 publications
(55 citation statements)
references
References 168 publications
(402 reference statements)
3
48
0
4
Order By: Relevance
“…Generally, onychomycosis may present as a mixture of clinical types, but the most common type is DLSO [7,16], and our study found that oral F-RVCZ therapy is effective for treating DLSO. In addition, F-RVCZ therapy exhibited e cacy against dermatophytoma, an intractable clinical feature.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…Generally, onychomycosis may present as a mixture of clinical types, but the most common type is DLSO [7,16], and our study found that oral F-RVCZ therapy is effective for treating DLSO. In addition, F-RVCZ therapy exhibited e cacy against dermatophytoma, an intractable clinical feature.…”
Section: Discussionsupporting
confidence: 51%
“…Therefore, proper treatments that completely cure onychomycosis would improve both clinical ndings and patient quality of life. According to several guidelines, systemic therapy is recommended for the treatment of onychomycosis [5][6][7]. Two oral antifungal agents, itraconazole and terbina ne hydrochloride, have a long history of use in Japan, and these agents received approval for insurance coverage for the treatment of onychomycosis in the 1990s.…”
Section: Introductionmentioning
confidence: 99%
“…1 To identify the true pathogen in onychomycosis, the guidelines and expert opinion recommend repeated examinations and the use of a combination of various diagnostic techniques. [1][2][3] The LFIA kit is generally cost-effective and easy and rapid to use for on-site diagnosis despite being more expensive than direct KOH microscopy. Its diagnostic value for tinea unguium depends on its sensitivity and specificity in comparison with direct KOH microscopy.…”
Section: Discussionmentioning
confidence: 99%
“…
Onychomycosis is a common fungal disease of the nails caused by dermatophytes, non-dermatophyte molds (NDM), and yeasts. [1][2][3] The term tinea unguium refers to a dermatophytic nail infection mainly caused by Trichophyton rubrum followed by Trichophyton interdigitale. Despite the widespread prevalence of onychomycosis, accurate methods of diagnosing this group of diseases and achieving a complete cure continue to be challenging.Various non-infectious nail disorders, including lichen planus, psoriasis, palmoplantar pustulosis (PPP), and pachyonychia clinically resemble onychomycosis.
…”
mentioning
confidence: 99%
See 1 more Smart Citation